Prarancangan Pabrik Metanol Dengan Proses Lurgi-Low Pressure Methanol Dengan Disain Alat Utama Reaktor Syntesis Methanol (R-03) - Saleh, Muhammad; Saputra, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Methanol is often called methyl alcohol with the chemical formula CH3OH. Methanol is commonly used for solvents, anti-freezing refrigerants, and fuels. Methanol is also an intermediate compound that is used as raw material for various industries including acetic acid, formaldehyde, MTBE, polyvinyl, polyester, and DME industries. The need for methanol in Indonesia continues to increase. The raw material used in this methanol plant design is natural gas. This methanol plant will operate for 330 days per year with a continuous work of 24 hours/day and a capacity of 200,000 tons/year which will be established in Dumai, Riau. The main equipment design in this plant is the Reactor Syntesis Methanol which functions to form methanol in the form of syntesis gas as carbon monoxide (CO), carbon dioxide (CO2) and hydrogen (H2) with the help of H2O. The Syntesis Methanol Reactor is operated at a pressure of 50 bar and a temperature of 250 Â° C. The economic analysis on the design of this plant shows that the Methanol plant with the Lurgi Low Pressure process is feasible to be built with the profit after tax of Rp8,190,624,006,578 and the factory Payback Period (PBP) of 3.1 years.Keywords: Lurgi Low Pressure Process, Methanol, Natural Gas, Syntesis Gas, Syntesis Methanol Reactor